Anatomy of the airways of Alouatta belzebul (Research, Society and Development, 2020)
Alouatta belzebul is a species of howler, from the Atelidae family and genus Alouatta, known as the red-handed Guariba. It is endemic in Brazil, occurring two populations: in the Amazon and the Atlantic Forest of the northeast coast. The anatomy of this genus presents variations among primates, such as atypical development of the larynx. These variations occur mainly by behavioral factors, defense of food and territory. This study established comparative data on the structures of the respiratory system, with that of other primates and mammals. In the larynx, the presence of muscles, membranes and ligaments was observed, in consonance with the structures observed in human primates, and a very evident hyoid bone. The trachea of the Alouatta Belzebul consists of 11 to 12 incomplete cartilaginous rings. In the pulmonary structures, there was a fourth lobe in the right lung, on the left, presenting only two wolves, which resembled other non-human primates, such as white-tufted Sagui (Callithrix Jacchus) and Capuchin monkey (Sapajus libidinosus), Domestic mammals such as canids and felines and wild mammals, such as Jaguatirica (Leopardus Pardalis) and Fox (Cerdocyon thous). The study contributed to a discussion about evolutionary aspects of the respiratory system and clinical and surgical performance of the veterinary physician.